Transmitted and acquired HIV drug resistance in Viet Nam - Thao, V (2015)
The roll-out of antiretroviral therapy (ART) in Viet Nam along with limited resources for treatment monitoring are expected to be accompanied by the emergence of transmitted and acquired drug resistance. Drug resistance challenges the success of ART program and the efforts to curb the HIV epidemic in Viet Nam. Understanding factors that impact treatment outcome and prevalence and patterns of drug resistance provides imperative information for strategic and effective management. The first part of this thesis aims to study the prevalence and patterns of transmitted drug resistance (TDR) in ART-naïve patients. TDR prevalence was detected in 6.4% of ARV-naïve patients with HIV-associated tuberculous meningitis initiating ART in Ho Chi Minh City (HCMC) from 2005-2007. This rate is lower than that in developed countries and is comparable to TDR rates reported in similar resource-limited countries. Pattern of TDR reflected the standard first-line ART regimens with nucleotide and non-nucleotide reverse transcriptase inhibitors in Viet Nam. The second part of this thesis aims to investigate factors that impact treatment outcome and drug resistance in second-line ART in Viet Nam. In a cohort of adult patients on second-line ART at the Hospital for Tropical Diseases, rate of clinical and/or immunological failure was 18.2% after a median follow up of 29 months. Older age, history of injecting drug use, lower CD4 count at second-line ART initiation, suboptimal ART adherence, and previous protease inhibitor (PI) use independently predicted treatment failure. Prevalence of virological failure (HIV RNA >1000 copies/mL as recommended by the 2013WHO guidelines) in patients who survived and were in active follow up was 9.5%, and high viral load, non-adherence and previous PI use were independent predictors for virological failure to second-line ART. 64% of patients with virological failure carried major PI mutations. Cross-resistance to third-line medications was higher than reported in other studies with cross resistance to ETR, TPV, and DRV of 55%, 45%, and 27% patients, respectively. This information informs selection of appropriate third-line ART regimen for patients failing second-line ART in Viet Nam. In conclusion, the work of this thesis provides important data on TDR in the chronically HIV-infected population in Viet Nam, provides, for the first time, data on treatment outcome to lopinavir-based second-line ART in the presence of extensive NRTI drug resistance, and identifies modifying risk factors to improve treatment outcomes in Viet Nam. Strategies to diagnose treatment failure accurately, to switch therapy timely, and to provide targeted adherence support will improve the outcomes of patients. Continued surveillance of TDR should be performed to assure the effectiveness of ART at the population level. Cost-effectiveness studies should be conducted in order to provide evidence for policy makers to decide whether to apply baseline genotypic testing and viral load monitoring in a resource limited country like Viet Nam. Prospective studies are needed to study the validity of WHO immunological/clinical criteria in defining virological treatment failure in PI-based second-line ART.